SYNTACTIC FUNCTIONS AND PATTERNS OF COMBINABILITY OF ADVERBS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
These article is about adverbs and their combinability whereas others may modify different words, for instance enoughwhich may be used in to -word enough , not quickly enough, quick enough.Kalit so'zlar: Adverb, vazifalar, jumlalar, adverbial modifikator, sintaktik, taqqoslash so'zlar, tinish belgilar.